Clinical researchThe effect of treatment on lipid peroxidation in patients with subarachnoid haemorrhage - Woźniak, Bartosz; Woźniak, Alina; Drewa, Gerard; Mila-Kierzenkowska, Celestyna; Ślusarz, Robert (Archives of Medical Science, 2009)
Introduction: Subarachnoid haemorrhage (SAH) is accompanied by increased generation of reactive oxygen species (ROS) and intensification of the lipid peroxidation. The aim of this study was to investigate the effect of treatment on the level of lipid peroxidation products: conjugated dienes (CD) and thiobarbituric acid-reactive substances (TBARS) in SAH patients’ peripheral blood plasma and erythrocytes. Material and methods: The study was performed on 42 SAH patients (Hunt and Hess grade I or II) and on 20 healthy volunteers (control). All SAH patients underwent surgery and pharmacotherapy (dexamethasone, omeprazole, cefuroxime, mannitol, nimodypine). Venous blood was taken from the SAH patients before surgical and pharmacological treatment, one day after and ten days after surgery, and once from the controls. Results: TBARS concentration in blood plasma and erythrocytes and CD level in erythrocytes of SAH patients before treatment was more than twice higher (p < 0.001) than in the controls, and CD level in blood plasma was almost three times as high (p < 0.001) as in the controls. One day after surgery, the concentration of these parameters decreased by about 20% (p < 0.001) compared to baseline level. Ten days after surgery, TBARS and CD concentration decreased two-fold (p < 0.001) compared to their level one day after surgery. Moreover, those values were not statistically significantly different as compared with the control group. Conclusions: Surgical and pharmacological treatment of SAH patients restored prooxidant-antioxidant balance. Evaluation of TBARS and CD level, in SAH patients’ peripheral blood may help to monitor the therapy efficiency in normalization of CNS oxygen metabolism.